a, \(\left(3+2x\right)^2=9+12x+4x^2\)
b, \(\left(3x-2y\right)^2=9x^2-12xy-4y^2\)
c, \(\left(2x-3y\right)\left(2x+3y\right)=4x^2+6xy-6xy-9y^2=4x^2-9y^2\)
d, \(\left(2x+3y\right)^3=8x^3+36x^2y+54xy^2+27y^3\)
( 3 + 2x )2 = 32 + 2.3.2x + ( 2x )2 = 4x2 + 12x + 9
( 3x - 2y )2 = ( 3x )2 - 2.3x.2y + ( 2y )2 = 9x2 - 12xy + 4y2
( 2x - 3y )( 2x + 3y ) = ( 2x )2 - ( 3y )2 = 4x2 - 9y2
( 2x + 3y )3 = ( 2x )3 + 3( 2x )2.3y + 3.2x.( 3y )2 + ( 3y )3 = 8x3 + 36x2y + 54xy2 + 27y3
Khai triển HĐT ?
a) \(\left(3+2x\right)^2=9+12x+4x^2\)
b) \(\left(3x-2y\right)^2=9x^2-12xy+4y^2\)
c) \(\left(2x-3y\right)\left(2x+3y\right)=4x^2-9y^2\)
d) \(\left(2x+3y\right)^3=8x^3+36x^2y+54xy^2+27y^3\)
Bài làm :
a) \(\left(3+2x\right)^2=9+12x+4x^2\)
b) \(\left(3x-2y\right)^2=9x^2-12xy+4y^2\)
c) \(\left(2x-3y\right)\left(2x+3y\right)=4x^2-9y^2\)
d) \(\left(2x+3y\right)^3=8x^3+36x^2y+54xy^2+27y^3\)
Chúc bạn học tốt !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
a,\(\left(3+2x\right)^2=9+12x+4x^2\)
b,\(\left(3x-2y\right)^2=9x^2-12xy+4y^2\)
c,\(\left(2x-3y\right)\left(2x+3y\right)=\left(2x\right)^2-\left(3y\right)^2=4x^2-9y^2\)
\(a,\left(3+2x\right)^2=9+12x+4x^2\)
\(b,\left(3x-2y\right)^2=9x^2-12xy+4y^2\)
\(c,\left(2x-3y\right).\left(2x+3y\right)=4x^2-9y^2\)
\(d,\left(2x+3y\right)^3=8x^3+36x^2y+54xy^2+27y^3\)